Nutritional composition of indigenous cultivar of black cumin seeds from Bangladesh - Kabir, Yearul; Shirakawa, Hitoshi; Komai, Michio (Progress in Nutrition, 2019)
Proximate analysis of black cumin (Nigella sativa L.) seeds showed a mean composition of 20.3% protein, 45.4% fat, 7.1% moisture, 7.4% ash and the rest being total carbohydrate. The fat and ash content were much higher than the value reported in the literature. Potassium, phosphorus, calcium, and magnesium were the predominant elements present. Sodium, iron, zinc, and copper were found at lower levels. Cadmium, lead, and molybdenum were also detected in trace levels. Linoleic acid (57%) followed by oleic acid (21.8%) were the major unsaturated fatty acids, while palmitic acid (13.1%) was the main saturated one. Glutamic acid (23.95%), aspartic acid (9.32%) and arginine (8.90%) were the main amino acids present while tryptophan and methionine were the minor amino acids. These results indicate the high nutritional potential of Bangladeshi black cumin seeds especially as a source of protein (20.3±0.63%) and fat (45.4±0.53%) especially unsaturated fatty acids (84%), which may be utilized as food supplements.